Nigerian Plant Resources, an Incredible Generosity with an Incredible Responsibility - Falusi, O.A. (Machakos University, 2018)
Nigeria is a physically and climatically diverse country that has been endowed with substantial plant resources. The natural vegetation varies from rain forest to savanna with nine distinct ecological zones which permit the growth of a wide variety of crops. The country is generously blessed with a lot of plant resources to the extent that, there will be no reason whatsoever to live in hunger or suffering. This magnanimity is an incredible generosity of Mother Nature which carries with it an equally incredible responsibility. This review paper attempts to highlight the value and incalculable magnanimity of Mother Nature in Nigerian Plant genetic resources. It also discusses the need to utilize the God-given plant genetic resources with responsibility and wise exploitation. Apparently, there is need for the scientific research community in every country to wake up to this reality and be engaged in not just knowing their heritage in plant genetic resources but also to do what is necessary to ensure food security in their country.
Keywords: Plant genetic resources; Natural vegetation; Incredible generosity; Incredible responsibility; Wise exploitation; Food security